Development of Community Boar Semen Production Center for Artificial Insemination to be Used by Smallholder Farmers in Tambon Muang Jang, Nan Province - Kaewlamun, Winai; Nitiwararuk, Kajohn; Tantasuparak, Wichai (Area Based Development Research Journal, 2019)
The majority of the pig farmers in the Tambon Muang Jang, in Nan Province are smallholder farmers and some of them have formed a pig production group. Farmers have been trained and are able to detect heat and perform artificial insemination (AI) in their sows. However, boars are not reared on the farm and therefore boar semen is not produced to do on-farm AI. When sows are observed to be in standing estrus, farmers use a cool box to fetch the boar semen from the Center of Learning Network for the Region (CLNR), Chulalongkorn University. Sometimes boar semen provision is lower than the demand and sometimes the sow shows signs of standing estrus at the weekend when the semen collection service is unavailable. Both problems lead to economic losses for the farmers because insemination cannot be performed. This study aims to create a community boar semen production center and produce high genetic boar semen to be used for artificial insemination in sows in the community. Farmer participation is recorded in all processes and activities within this study. The project starts by gathering farmer data and information in order to understand farmers and their needs. Boar semen collection and a preparation training course are organized to train a selected number of farmers. Boar housing and an artificial insemination laboratory is established. A steering committee is formed to manage the community boar semen production center. The project succeeds in training four farmers who have passed the training course. They have obtained the skills necessary to produce chilled boar semen for artificial insemination. Two high genetic boars are introduced into the community boar semen production center for semen collection. When operating, the center provides 135 individual farmers with 2 doses of chilled semen per time to inseminate their sows during September 2014 – October 2016. The results of the project have an impact on the socio-economics of the farmers by avoiding economic losses from insufficient semen production. The community boar semen production center is located in the community which means that farmers do not waste time going to the CLNR. This center can be a self-reliant model for community boar semen production that is applicable to other communities.